1990
DOI: 10.1111/j.1365-2230.1990.tb02074.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative double-blind study of terbinafine (Lamisil) and griseofulvin in tinea corporis and tinea cruris

Abstract: In a double-blind randomized study, 92 patients with culturally proven tinea corporis and/or tinea cruris were treated orally with either terbinafine (Lamisil) (125 mg b.i.d.) or griseofulvin (500 mg b.i.d.) for up to 6 weeks. The two groups of patients and distribution of the target lesions were similar, but the analysis of the clinical scores showed that the terbinafine group had slightly higher mean scores at baseline (P = 0.186). At the end of therapy the proportion of patients with negative microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Complaints reported by investigators have included nausea, dyspepsia, abdominal pain or cramping, stomach pains, diarrhoea, and soft or frequent stools (Cole & Stricklin 1989;Del Palacio et al 1990;Goodfield et al 1989;Hay et al 1991;Savin 1989;Savin & Zaias 1990; Villars ;Zaias 1990), which rarely required discontinuation of the drug (Del Palacio et al 1990;Goodfield et al 1989;Hay et al 1991).…”
Section: Gastrointestinalmentioning
confidence: 96%
“…Complaints reported by investigators have included nausea, dyspepsia, abdominal pain or cramping, stomach pains, diarrhoea, and soft or frequent stools (Cole & Stricklin 1989;Del Palacio et al 1990;Goodfield et al 1989;Hay et al 1991;Savin 1989;Savin & Zaias 1990; Villars ;Zaias 1990), which rarely required discontinuation of the drug (Del Palacio et al 1990;Goodfield et al 1989;Hay et al 1991).…”
Section: Gastrointestinalmentioning
confidence: 96%
“…84 Following oral administration for the treatment of tinea corporis and tinea cruris, clinical and mycological cure rates observed with terbinafi ne have ranged from 71% to 100% and 78% to 100%, respectively. 78,[87][88][89] No signifi cant differences in mycological or clinical cure rates were observed between terbinafi ne and griseofulvin in these studies; [87][88][89] however, higher relapse rates were observed with griseofulvin. 88,89 Tinea imbricata, a variant of tinea corporis found predominantly in tropical countries, manifests as concentric rings of papular plaques that are chronic in nature and relatively recalcitrant to antifungal therapy.…”
Section: Cutaneous Dermatophytosesmentioning
confidence: 99%
“…78,[87][88][89] No signifi cant differences in mycological or clinical cure rates were observed between terbinafi ne and griseofulvin in these studies; [87][88][89] however, higher relapse rates were observed with griseofulvin. 88,89 Tinea imbricata, a variant of tinea corporis found predominantly in tropical countries, manifests as concentric rings of papular plaques that are chronic in nature and relatively recalcitrant to antifungal therapy. In a single randomized, controlled trial 4 weeks of treatment with terbinafi ne demonstrated higher overall effi cacy rates (100%) and lower relapse rates (16%) as compared with itraconazole (89% effi cacy, 75% relapse).…”
Section: Cutaneous Dermatophytosesmentioning
confidence: 99%
“…The efficacy and safety of twice or three times a day topical preparations of TCZ solution appear to be similar to those of TCZ cream and clotrimazole solution. [15][16][17][18] Pharmacokinetic studies in rats have demonstrated minimal systemic exposure following dermal application of TCZ cream.2) After a single application of TCZ cream about 16% of the applied radioactivity penetrates into rat skin and the percutaneous penetration into swine skin is considerably higher than that of clotrimazole cream.19) BFZ also penetrates far better into human skin than clotrimazole. 20) Clinical trials have clearly demonstrated the efficacy and safety of various formulations of BFZ applied once a daily in the treatment of superficial fungal infections of the skin.…”
mentioning
confidence: 99%
“…The efficacy and safety of twice or three times a day topical preparations of TCZ solution appear to be similar to those of TCZ cream and clotrimazole solution. [15][16][17][18] Pharmacokinetic studies in rats have demonstrated minimal systemic exposure following dermal application of TCZ cream.…”
mentioning
confidence: 99%